Editorial - Nassaji, Hossein (Studies in Second Language Learning and Teaching, 2016)
The focus of this special issue is instructed second language acquisition (ISLA). It is to explore some of the most recent developments in this area of SLA research and its implications for classroom instruction. Drawing on some current definitions (Leow, 2015; Loewen, 2015; Nassaji, 2015; Nassaji & Fotos, 2010), ISLA is defined as an area of SLA that investigates not only the effects but also the processes and mechanisms involved in any form-focused intervention (explicit or implicit) with the aim of facilitating language learning and development. Instructed SLA differs from naturalistic SLA, which refers to second language (L2) acquisition taking place through exposure to language in naturalistic language learning settings with no formal intervention (Doughty, 2003). It is also different from classroom instruction with no focus on form. Furthermore, although instructed SLA is often taken to refer to what is learned inside the classroom, instructed SLA can also take place outside the classroom through, for xample, various instructional strategies (such as feedback, tasks, or explanation) that are often associated with instruction. Of course, this does not mean that the processes involved in SLA in and outside the classroom are exactly the same. Although there might be commonalities in learning processes, the classroom context has its unique features that might have an impact on learning. For example, in classroom learning a group of learners come together in a particular place to learn the language jointly during a given period of time. This might have an impact on learning opportunities in terms of the nature of the discourse created, learners’ participation, interaction, and engagement with language. As Allwright (1984, p. 156) pointed out, language interaction in the classroom setting is collectively constructed by all learners and “the importance of interaction in classroom learning is precisely that it entails this joint management of learning.”